Trans‐esophagogastric junction pressure gradients during straight leg raise maneuver on high‐resolution manometry associate with large hiatus hernias. Issue 7 (12th March 2020) - Rogers, Benjamin; Hasak, Stephen; Hansalia, Vivek; Gyawali, C. Prakash
Abstract: Background: Straight leg raise (SLR) while supine increases intra‐abdominal pressure. We hypothesized that elevations in intra‐abdominal pressure would transmit into the thoracic cavity if the esophagogastric junction (EGJ) was disrupted. Methods: Consecutive patients undergoing esophageal HRM were included if they had adequate SLR (hip flexion with knees extended for ≥ 5 seconds while supine). EGJ morphology was subtyped based on lower esophageal sphincter (LES) and crural diaphragm (CD) location (type 1: LES and CD overlap; type 2: separation of < 3 cm; type 3: separation of ≥ 3 cm). EGJ tone was assessed using EGJ contractile integral (EGJ‐CI). HRM studies were analyzed according to Chicago Classification v3.0. Mean and peak intra‐thoracic and abdominal pressures were measured at baseline and during SLR using on‐screen software tools. Trans‐EGJ gradients were compared, and pressure gradient < 1 mmHg denoted the equalization of pressures. Key Results: Of 430 patients, 248 (57.5 ± 0.9 years, 69.4% F) completed SLR. EGJ morphology was type 1 in 122 (49.2%), type 2 in 56 (22.6%) and type 3 in 40 (16.1%). In types 1 and 2 EGJ, neither the mean nor peak trans‐EGJ pressure gradient changed with SLR ( P ≥ .17 for each). In contrast, in type 3 EGJ, peak pressure gradient decreased significantly following SLR (3.5 ± 1.8 mmHg vs. −8.6 ± 4.8 mmHg, P = .01). More type 3 EGJ patients equalized peak (65%) pressures across EGJ compared with types 1 and 2 (27%, P < .001). Conclusions and Inferences: The evaluation of intra‐abdominal and intra‐thoracic pressures with SLR during esophageal HRM can provide evidence of physiological disruption of the EGJ barrier. Abstract : During the straight leg raise (SLR) maneuver during high resolution manometry (HRM), intra‐abdominal pressure transmits into the intra‐thoracic cavity when the esophagogastric junction (EGJ) is physiologically disrupted, particularly with large hiatus hernias (type 3 EGJ). SLR is therefore a simple provocative test to evaluate integrity of the EGJ barrier during HRM.